Estrategias Metodológicas para desarrollar las Conciencias Lingüísticas en los niños del subnivel de preparatoria de la Unidad Educativa Ana Páez de la parroquia Eloy Alfaro, cantón Latacunga durante el año lectivo 2022 2023. - Chiguano Sandoval, Mayra Alexandra (2023)
The educational institution where this research was carried out hosts a large number of indigenous migrant population from rural areas, which, due to their culture, language and especially the precarious economic conditions and sub-employment, have led to parents being absent from their homes. . Depriving children of the necessary accompaniment, to facilitate learning, to this is added, that teachers do not apply motivating strategies and techniques for the development of linguistic awareness, which are important in childhood since the child must understand and discover the relationship within the formation of oral language and the function in words. The present investigation was carried out with the objective of potentiating the development of linguistic awareness through methodological strategies to improve orality in children of the high school sublevel.